Endodontic management of a maxillaryfirst molar with three palatal canals - A case report - Osama Adeel Khan Sherwani; Ashok Kumar; Rajendra Kumar Tewari; Surendra Kumar Mishra; Sajid Ali (Wolters Kluwer Medknow Publications, 2015)
This case report presents a successful endodontic management of left maxillaryfirst molar with three palatal canals. This rare root canal morphology was diagnosed using dental operating microscope (DOM) and confirmed with cone beam computed tomography (CBCT). Axial CBCT images confirmed that the palatal canals merged with each other in the apical third and exited through one apical foramen. This report highlights the importance of magnification (DOM) and advanced imaging techniques (CBCT) in better understanding of complex Root canal anatomy.